TREATMENT WITH IMATINIB MESILAT IN CHRONIC MYELOGENOUS LEUKEMIA – OUR EXPERIENCE - Mateja Grat; Joško Vučkovič (Zdravniški Vestnik, 2004)
Background. Chronic myelogenous leukemia (CML) is a malignant clonal disorder of hematopoietic stem cell. In majority of patients we find reciprocal chromosomal translocation t (9.22) which result in fusion oncoprotein with tyrosine kinase activity. The normal ABL protein is involved in the regulation of the cell cycle. Fusion oncoprotein deregulates signal transducing pathways, causing an abnormal cell cycling, inhibition of apoptosis and increased proliferation of cells. ABL specific tyrosin kinase inhibitors selectively inhibit the growth of BCR-ABL positive cells. Methods. Eleven patients with chronic phase CML were treated with 400 mg of oral imatinib daily. Patients were evaluated for cytogenetic and hematologic responses and toxic effects. Results. Imatinib induced major cytogenetic response (MCR) in 78% and a complete hematologic response (CHR) in 100% of eleven patients. We observe non hematologic toxic effects in 55% and grade 3 or 4 hematologic toxic effects in 11% of patients. Conclusions. Imatinib induced high rates of cytogenetic and hematologic responses in patients with chronic phase CML.